Pasir Kencana Beach Tourism Management System Pekalongan City - Santoso, Rohman Eko; Mahendriya, Ginanjar (TERRACE: JOURNAL OF ARCHITECTURE & URBAN STUDIES, 2024)
Abstract. One of the tourism potentials located in Pekalongan City is Pasir Kencana Beach which is located in Panjang Wetan Village, North Pekalongan District. Pasir Kencana Beach is approximately ±4km or approximately ±15 minutes from the center of Pekalongan City. This beach has previously attracted a lot of interest from local and out-of-town tourists because of its beautiful sunset views in the afternoon. The Golden Sands tourist location is close to the port, fish auctions and nearby beach tourist attractions so it is very strategic and easy to reach. Pasir Kencana Beach is generally used as a family tourist destination. Golden sand beach used to have an area of beach sand that sparkled like gold, but as sea levels rose or tidal disasters caused the embankments to be damaged, some facilities were poorly maintained and the playground area was submerged when heavy rains arrived, so revitalization or repair of tourist attractions was needed to bring them back to life. Beach tourism can increase the number of visitors and economic growth in the surrounding area. In an effort to support the development of the Marine Tourism Area in the Pekalongan City area into an integrated beach tourism destination, a development concept is needed through infrastructure development which includes aspects of Accessibility, Amenities and Attractions (3A). The infrastructure development components include repairing roads to tourist areas, structuring coastal tourist areas which include facilities and infrastructure supporting the area such as: construction of public spaces (rest areas, parking, ticketing, play areas, toilets, landmarks, green open spaces, street furniture, as well as management of drainage, solid waste, waste and others.